Characteristics and a comparison of the gut microbiota in two frog species at the beginning and end of hibernation - Tong, Qing; Dong, Wen-jing; Xu, Ming-da; Hu, Zong-fu; Guo, Peng; Han, Xiao-yun; Cui, Li-yong (Frontiers in Microbiology, 2023)
Season has been suggested to contribute to variation in the gut microbiota of animals. The complicated relationships between amphibians and their gut microbiota and how they change throughout the year require more research. Short-term and long-term hypothermic fasting of amphibians may affect gut microbiota differently; however, these changes have not been explored. In this study, the composition and characteristics of the gut microbiota of R. amurensis and R. dybowskii during summer, autumn (short-term fasting) and winter (long-term fasting) were studied by high-throughput Illumina sequencing. Both frog species had higher gut microbiota alpha diversity in summer than autumn and winter, but no significant variations between autumn and spring. The summer, autumn, and spring gut microbiotas of both species differed, as did the autumn and winter microbiomes. In summer, autumn and winter, the dominant phyla in the gut microbiota of both species were Firmicutes, Proteobacteria, Bacteroidetes, and Actinobacteria. All animals have 10 OTUs (> 90% of all 52 frogs). Both species had 23 OTUs (> 90% of all 28 frogs) in winter, accounting for 47.49 ± 3.84% and 63.17 ± 3.69% of their relative abundance, respectively. PICRUSt2 analysis showed that the predominant functions of the gut microbiota in these two Rana were focused on carbohydrate metabolism, Global and overview maps, Glycan biosynthesis metabolism, membrane transport, and replication and repair, translation. The BugBase analysis estimated that among the seasons in the R. amurensis group, Facultatively_Anaerobic, Forms_Biofilms, Gram_Negative, Gram_Positive, Potentially_Pathogenic were significantly different. However, there was no difference for R. dybowskii. The research will reveal how the gut microbiota of amphibians adapts to environmental changes during hibernation, aid in the conservation of endangered amphibians, particularly those that hibernate, and advance microbiota research by elucidating the role of microbiota under various physiological states and environmental conditions.